Aplikasi Penggunaan Resin Silika Gel-GPTMS Termodifikasi Dimetilamina untuk Analisis Ion Klorida (Cl⁻) secara Kromatografi Ion - Siska Maharani; Budhi Oktavia (Lembaga Yasin AlSys, 2025)
The limited use of silica gel as an ion-exchange resin in ion chromatography columns forms the background of this study, despite its high potential as a stationary phase. This research aims to apply glycidoxypropyltrimethoxysilane–dimethylamine (GPTMS–DMA) modified silica gel as an ion-exchange resin in ion chromatography for the analysis of chloride ions (Cl⁻). A quantitative method was employed, using chloride ion concentrations of 100 ppm, 200 ppm, and 300 ppm. The analysis was conducted using High Performance Liquid Chromatography (HPLC) with a column packed with GPTMS–DMA silica gel and a mixed eluent of Na₂CO₃ and NaHCO₃ at concentrations of 0.1 M, 0.05 M, and 0.01 M. The results showed that 0.1 M Na₂CO₃ produced the most optimal chromatogram peaks, with a regression equation of y = 0.0004x and a determination coefficient R² = 0.9733, indicating high linearity. The study concludes that GPTMS–DMA modified silica gel is effective as a stationary phase for chloride ion analysis via ion chromatography and holds strong potential for further development as an ion-exchange resin in broader chemical analysis applications.